2020
DOI: 10.3390/ijerph17249313
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review of How Income Affects Accessing Local Green Space to Engage in Outdoor Physical Activity to Improve Well-Being: Implications for Post-COVID-19

Abstract: Background: The National Institute for Health and Care Excellence (NICE) has set out guidance for promoting physical activity (PA) in the physical environment to promote health and well-being. The aim of this selective scoping review was to investigate the influence of gross income on accessing local green spaces to engage in PA and the associated health benefits. Methods: A scoping review was conducted of international literature to facilitate the clarification of the research question. Findings: 15 papers we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…Echoing the current study's findings, a European study found that having green-blue nature views from the home was associated with fewer symptoms of depression and anxiety [61], and in Bulgaria, visible greenery from the home was associated with reduced depressive/anxiety symptoms [62]. Nature-based engagement in a private green space [63], near home [56], in local green spaces [64], or even within the home (e.g., houseplants) [62] have all been shown to support mental health in other global research during the pandemic. In the current study, some of the more passive forms of nature contact were the most commonly reported alternatives to outdoor nature experiences, and included indoor bird watching, listening to birdsong, and smelling rain or plants.…”
Section: Discussionsupporting
confidence: 68%
“…Echoing the current study's findings, a European study found that having green-blue nature views from the home was associated with fewer symptoms of depression and anxiety [61], and in Bulgaria, visible greenery from the home was associated with reduced depressive/anxiety symptoms [62]. Nature-based engagement in a private green space [63], near home [56], in local green spaces [64], or even within the home (e.g., houseplants) [62] have all been shown to support mental health in other global research during the pandemic. In the current study, some of the more passive forms of nature contact were the most commonly reported alternatives to outdoor nature experiences, and included indoor bird watching, listening to birdsong, and smelling rain or plants.…”
Section: Discussionsupporting
confidence: 68%
“…Another report from the U.S. showed that stayat-home orders have affected vulnerable groups who live in highly dense areas more than less vulnerable groups who have access to urban nature close to their homes (Slater et al, 2020). People who live in lower socio-economic areas tend to be more sedentary and face greater issues with access to green spaces (see Spencer et al, 2020 for a review). Also, vulnerable populations tend to contract COVID-19 at higher rates than less vulnerable people (Slater et al, 2020) and are disproportionately dying from the disease (Centers Disease Control Prevention., 2020;Yancy, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Since China has adopted unified isolation management measures for people infected with COVID-19, the subjects of the investigation were those who were not infected with COVID-19. The participants were divided into the following ten groups based on their age: 17 3), geographic location (province and city), occupation (Table 4), and region (town and village) of the participants.…”
Section: The Study Populationmentioning
confidence: 99%
“…Recent studies also have shown that there is a severe lack of PA guidance and mitigation strategies to advance the knowledge and role of PA to improve physical and mental health in most countries during the epidemic [15]. On the whole, existing studies have mainly revealed this phenomenon that there was a high prevalence of physical inactivity due to the outbreak of the pandemic and analyzed the importance of strengthening proper PA to promote physical and mental health and prevent epidemics [16][17][18]. However, a series of crucial questions need to be answered: Is the PA of all groups affected during the epidemic?…”
Section: Introductionmentioning
confidence: 99%